PERTIMBANGAN HAKIM TERHADAP KEDUDUKAN SAKSI MAHKOTA DALAM PERKARA TINDAK PIDANA KORUPSI YANG DILAKUKAN JULIARI BATUBARA: - - Maria Amalia Farentchois Sani Asa; Dian Adriawan Dg Tawang (Reformasi Hukum Trisakti, 2023)
Law enforcement in the case of criminal acts of corruption committed by Juliari Batubara involved various problems. One of them is related to the judge's consideration of presenting a crown witness at the trial who actually had sufficient evidence at the trial. This is not in accordance with the Supreme Court Circular Number 05 of 2014. In the discussion the author will focus on the analysis of the judge's considerations in decision number: 29/Pid.Sus-Tpk/2021/PN.Jkt Pst based on evidence according to the procedural law book Criminal. The research method used by the author is Normative Juridical, and is descriptive in nature so that data collection is carried out by literature study to produce conclusions in a deductive manner. Based on the author's analysis, the panel of judges' considerations regarding the use of crown witnesses in the Covid-19 Social Assistance Corruption crime case did not meet the requirements as evidence, but what was presented at trial was sufficient, in fact this could provide an opportunity for the defendant to have his sentence reduced. Apart from that, there is a discrepancy with the provisions of the Criminal Procedure Code (KUHAP). Therefore, the author suggests that there is a need for a review of crown witnesses who are presented in the trial process for criminal acts of corruption, so that judges can provide more appropriate decisions by considering all the evidence and witness statements presented in a case.